Predictors of Compliance to Gluten-Free Diet in Children with Celiac Disease - Garg, Anu (Int Sch Res Notices, 2014)
Aim. To identify the predictors of compliance to gluten free diet in children with celiac disease. Methods. 134 children in the study group were assessed for dietary compliance followed by a questionnaire based interview. Psychosocial parameters were assessed by standard Pediatric Symptom Checklist (PSC). Dietary compliant and noncompliant groups were compared and assessed for factors affecting the dietary compliance. Predictability of all of these factors was assessed using binary logistic regression analysis with backward elimination to find out the best predictors of compliance. Results. In the study group, 88 (65.67%) were found to be strictly compliant. Factors that were found to be significantly associated with compliance were age at presentation, nuclear families, mother's education, and parents having better knowledge of celiac disease. Parents' and child's attitude towards his having to follow a restrictive diet and child's feelings were also shown to be significantly associated with compliance. Binary logistic regression analysis with backward elimination demonstrated that age at presentation, family type, child's attitude, and child's behaviour made a significant contribution to prediction. Conclusions. These results will contribute to the current body of research by providing health care practitioners with a framework for better dietary instruction to ensure maximum adherence to GFD.